Board Composition and Outreach Performance of Microfinance Institutions: Evidence from East Africa1. (January 2015) - Mori, Neema; Golesorkhi, Sougand; Randøy, Trond; Hermes, Niels
<x xml:space="preserve">Abstract</x> The attributes of microfinance's board members have an impact on attainment of their social objectives.